The Senses Considered as Perceptual Systems - Gibson, James J. 1904-1979 (Boston Houghton Mifflin, 1966)
It has always been assumed that the senses were channels of sensation. To consider them as systems for perception, as this book proposes to do, may sound strange. But the fact is that there are two different meanings of the verb to sense, first, to detect something, and second, to have a sensation. When the senses are considered as perceptual systems the first meaning of the term is being used.In the second meaning of the term there is a vast difference between sensations and perceptions. In 1785, Thomas Reid wrote:The external senses have a double providence; to make us feel, and to make us perceive. They furnish us with a variety of sensations, some pleasant, others painful, and others indifferent; at the same time they give us a conception, and an invincible belief of the existence of external objects. This conception of external objects is the work of nature. The belief of their existence, which our senses give, is the work of nature; so likewise is the sensation that accompanies it. This conception and belief which nature produces by means of the senses we call perception. The feeling which goes along with the perception, we call sensation. The perception and its corresponding sensation are produced at the same time. In our experience we never find them disjoined. Hence we are led to consider them as one thing, to give them one name, and to confound their different attributes. It becomes very difficult to separate them in thought, to attend to each by itself, and to attribute nothing to it which belongs to the other (Essays on the Intellectual Powers of Man, II, p. 17).That province of the senses which is to "furnish us with a variety of sensations" is by no means the same as that which is to "make us perceive." Reid was right. The part of this passage that might be objected [p.2] to is the suggestion that perception of objects must depend on "conception and belief." It will here be suggested that the senses can obtain information about objects in the world without the intervention of an intellectual process -or at least that they can do so when they operate as perceptual systems.In this book I will distinguish the input to the nervous system that evokes conscious sensation from the input that evokes perception. I will not even speak of the ingoing impulses in nerves as "sensory," so as not to imply that all inputs arouse sense impressions. For it is surely a fact that detecting something can sometimes occur without the accompaniment of sense impressions. An example is the visual detection of one thing behind another, which is described in Chapter 10. There will be many examples of the principle that stimulus information can determine perception without having to enter consciousness in the form of sensation.The reader should make allowance for the double meaning of the verb to sense. The detecting of stimulus information without any awareness of what sense organ has been excited, or of the quality of the receptor, can be described as "sensationless perception." But this does not mean that perception can occur without stimulation of receptors; it only means that organs of perception are sometimes stimulated in such a way that they are not specified in consciousness. Perception cannot be "extrasensory," if that means without any input; it can only be so if that means without awareness of the visual, auditory, or other quality of the input. An example of this is the "obstacle sense" of the blind, which is felt as "facial vision" but is actually auditory echo detection. The blind man "senses" the wall in front of him without realizing what sense has been stimulated. In short, there can be sensationless perception, but not informationless perception.The seemingly paradoxical assertion will be made that perception is not based on sensation. That is, it is not based on having sensations, as in the second meaning, but it is surely based on detecting information, as in the first meaning.There are two different levels of sensitivity. It will be evident in Chapter 2 that the so-called sense organs are of at least two different sorts: the passive receptors that respond each to its appropriate form of energy, and the active perceptual organs, better called systems, that can search out the information in stimulus energy. The receptors have measurable thresholds below which they are not excited; the organs and systems do not have fixed thresholds except as they depend on receptors.Similarly, there are different levels of stimulation. The stimulus energy of optics, mechanics, and chemistry is coordinate with receptors, but the stimulus information to be described is coordinate with perceptual systems. Stimulus energy varies along simple dimensions like intensity and [p.3] frequency, but stimulus information varies along innumerable complex dimensions, not all amenable to physical measurement.When the senses are considered as channels of sensation (and this is how the physiologist, the psychologist, and the philosopher have considered them), one is thinking of the passive receptors and the energies that stimulate them, the sensitive elements in the eyes, ears, nose, mouth, and skin. The experimenters in physiology and psychology have been establishing the conditions and limits at this level of stimulation for more than a century. A vast literature of sensory physiology has developed and a great deal is known about the receptors. It is a highly respected branch of science. But all this exact knowledge of sensation is vaguely unsatisfactory since it does not explain how animals and men accomplish sense perception.It can be shown that the easily measured variables of stimulus energy, the intensity of light, sound, odor, and touch, for example, vary from place to place and from time to time as the individual goes about his business in the environment. The stimulation of receptors and the presumed sensations therefore, are variable and changing in the extreme, unless they are experimentally controlled in a laboratory. The unanswered question of sense perception is how an observer, animal or human, can obtain constant perceptions in everyday life on the basis of these continually changing sensations. For the fact is that animals and men do perceive and respond to the permanent properties of the environment as well as to the changes in it.Besides the changes in stimuli from place to place and from time to time, it can also be shown that certain higher-order variables of stimulus energy -ratios and proportions for example- do not change. They remain invariant with movements of the observer and with changes in the intensity of stimulation. The description of such stimulus invariants is a main concern of the chapters to follow. And it will be shown that these invariants of the energy flux at the receptors of an organism correspond to the permanent properties of the environment. They constitute, therefore, information about the permanent environment.The active observer gets invariant perceptions despite varying sensations. He perceives a constant object by vision despite changing sensations of light; he perceives a constant object by feel despite changing sensations of pressure; he perceives the same source of sound despite changing sensations of loudness in his ears. The hypothesis is that constant perception depends on the ability of the individual to detect the invariants, and that he ordinarily pays no attention whatever to the flux of changing sensations.The ways in which animals and men pick up information by looking, listening, sniffing, tasting, and touching are the subject of this book. [p.4] These five perceptual systems overlap one another; they are not mutually exclusive. They often focus on the same information -that is, the same information can be picked up by a combination of perceptual systems working together as well as by one perceptual system working alone. The eyes, ears, nose, mouth, and skin can orient, explore, and investigate. When thus active they are neither passive senses nor channels of sensory quality, but ways of paying attention to whatever is constant in the changing stimulation. In exploratory looking, tasting, and touching the sense impressions are incidental symptoms of the exploration, and what gets isolated is information about the object looked at, tasted, or touched. The movements of the eyes, the mouth, and the hands, in fact, seem to keep changing the input at the receptive level, the input of sensation, just so as to isolate over time the invariants of the input at the level of the perceptual system.The Senses and the Sensory NervesWhat about the input of the sensory nerves? We have been taught that the impulses in these fiber bundles comprised the messages of sense and that they were the only possible basis for perception. This doctrine is so generally accepted that to challenge it seems to fly in the face of physiology. There is said to be a receptor mosai
Keywords: Philosophy